2019
DOI: 10.19136/era.a6n16.1872
|View full text |Cite
|
Sign up to set email alerts
|

Productividad de ovejas Pelibuey y Katahdin en el trópico húmedo

Abstract: Nota científica recibida: 02 de junio de 2018 aceptada: 10 de octubre de 2018 RESUMEN. El objetivo del estudio fue evaluar variables de productividad en el periodo pre-destete de ovejas Pelibuey (n = 28) y Katahdin (n = 21) mantenidas en condiciones de producción del trópico húmedo. Las ovejas se colocaron junto con sus crías en corrales individuales del parto al destete. El consumo de materia seca (CMS) pre-destete y la productividad al destete no difirió (p > 0.05) entre razas, pero las ovejas Pelibuey tuvie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 20 publications
0
5
1
4
Order By: Relevance
“…The BMI has been widely used to estimate the percentage of fat in production animals and helps in the development of nutritional strategies to increase their productive and reproductive rates (Morley and Murray 2014;Urrutia-Morales et al 2016;Vaz et al 2022). In sheep, USM are also used to estimate carcass characteristics (Aguilar-Hernández et al 2016;Chay-Canul et al 2019) and body fat deposits (Chay-Canul et al 2016;Morales -Martínez et al 2019). However, with this study, we propose the association of BMI with USM, aiming at more precise and accurate estimates of internal fat deposits.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The BMI has been widely used to estimate the percentage of fat in production animals and helps in the development of nutritional strategies to increase their productive and reproductive rates (Morley and Murray 2014;Urrutia-Morales et al 2016;Vaz et al 2022). In sheep, USM are also used to estimate carcass characteristics (Aguilar-Hernández et al 2016;Chay-Canul et al 2019) and body fat deposits (Chay-Canul et al 2016;Morales -Martínez et al 2019). However, with this study, we propose the association of BMI with USM, aiming at more precise and accurate estimates of internal fat deposits.…”
Section: Discussionmentioning
confidence: 89%
“…The subcutaneous fat thickness (SFT) and thoracic Longissimus dorsi area (LDMA) were determined using Chison ® B-mode real-time ultrasound equipment (Medical Imaging Co., Ltd.; Wuxi, Jiangsu, China) with a 5-MHz linear probe. Previously, the sheep had been shaved between the 12th and 13th thoracic vertebrae and the 3rd and 4th lumbar vertebrae as described by Aguilar-Hernández et al (2016) and Chay-Canul et al (2016). Additionally, the maximum length of the Longissimus muscle (A) and the maximum depth of the Longissimus muscle (B) were measured as described by Härter et al (2014).…”
Section: Ultrasound Measurementsmentioning
confidence: 99%
“…Additionally, studies carried out in the arid and dry region of northwestern Mexico during the summer season have documented that high temperatures do not drastically reduce the productive capacity of the Pelibuey, Katahdin, and Dorper hair breed sheep, as well as their crosses (Macías et al, 2013;Macías et al, 2016). For their part, Chay et al (2019) reported that the combination of prolificacy with the low mortality rate of lambs in the pre-weaning period is an essential factor that favors productivity in Pelibuey and Katahdin sheep breeds. Consequently, these animals have high productive and reproductive potential in any region of the country.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, breed groups such as Katahdin and Dorper are used as parental breeds in some commercial herds (Oliva et al, 2002;Nava et al, 2006). However, Chay et al (2019) mentioned that the birth weight and pre-weaning development of lambs of the Pelibuey breed are lower than in other breeds, such as Katahdin and Dorper Hinojosa et al, 2015). Even though the Blackbelly and Pelibuey breeds have lower productive performance, it is necessary to evaluate their behavior in sheep production systems located in different regions of the country, both as a pure breed and in different crossbreeding systems with Dorper and Katahdin (Bores et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…En México, la producción de corderos se considera una fuente importante de ingresos, para lo cual se han realizado estrategias con el fin de incrementar la rentabilidad de las unidades de producción (UP), mediante la introducción de razas de ovinos, que ayuden a mejorar las variables reproductivas (Chay-Canul, 2019). La introducción de razas como la Katahdin, permitió aumentar la habilidad materna, los pesos al nacimiento y al destete y, la velocidad de crecimiento, en comparación a la raza Pelibuey (Notter, 2000).…”
Section: Introductionunclassified